THU0126 Dose Titration of Biologics for The Treatment of Rheumatoid Arthritis and Ankylosing Spondylitis: A Systematic Literature Review. (15th July 2016) - Lau, C.S.; Gibofsky, A.; Damjanov, N.; Lula, S.; Marshall, L.; Jones, H.; Emery, P.
Abstract : Background: Increasingly, clinicians treating rheumatoid arthritis (RA) or ankylosing spondylitis (AS) are trying to dose-titrate biologics, due to cost, patient preference, and safety. Recent clinical guidelines recommend down titration for RA. However, evidence of safety and efficacy is limited. Objectives: Conduct a systematic literature review to assess breadth and quality of published data and evaluate whether sufficient evidence exists to support dose titration of biologics in RA or AS. Methods: Medline, Embase, and the Cochrane library were electronically searched on February 2, 2015, and conference abstracts from 2010 to November 2015 were hand searched. Eligible studies included: randomized controlled trials (RCTs), non-RCTs, observational, and pharmacoeconomics. Biologics included: abatacept, adalimumab, certolizumab, etanercept, golimumab, infliximab, rituximab and tocilizumab. Outcomes were (1) efficacy and sustained remission, (2) flares and retreatment, (3) economic impact. Results: The search yielded 21, 585 records; after screening, 73 studies in 90 publications/abstracts were retained, including 15 full-text RCTs, 15 full-text non-RCTs and 43 conference abstracts. Efficacy and economic data were limited. Heterogeneity in disease duration, dosing strategies, and definition of treatment success/failure complicated the interpretation and comparison of regimens. Dose titration rationale varied greatly, and few studies used established definitions of flare (table). Level of evidence was low, with most studies presented as conference abstracts. Conclusions: Studies evaluating dose titration of biologics are heterogeneous in design and lack standardized definitions. Little evidence of safety and efficacy exists to support dose titration of biologics in RA or AS; RCTs with defined indicators of treatment success and failure are needed. Disclosure of Interest: C. S. Lau Consultant for: Abbvie, Astrazeneca, GlaxoSmithKline and Human Genome Sciences, Pfizer, Roche, UCB, A. Gibofsky Shareholder of: AbbVie, Angen, Celgene, Pfizer, GSK, J&J, Regeneron, Consultant for: AbbVie, Celgene, Pfizer, Iroko, Horizon, Samumed, Relburn, Speakers bureau: Amgen, AbbVie, Pfizer, Celgene, Iroko, Horizon, N. Damjanov Consultant for: Pfizer, Roche, MSD, Abbvie, Gedeon-Richter, Boehringer Ingelheim, S. Lula Employee of: Envision Pharma, L. Marshall Shareholder of: Pfizer, Employee of: Pfizer, H. Jones Shareholder of: Pfizer, Employee of: Pfizer, P. Emery Consultant for: Pfizer, MSD, Abbvie, BMS, UCB, Roche, Novartis, Samsung, Sandoz and Lilly